Rivale: A Prototype realistic Immersive Virtual Agent-Based Learning Environment Case Study for Learning Requirements Elicitation Skills - Riedman, P.; Venable, John; Chang, Vanessa; Reiners, Torsten; Guetl, Christian (AIS, 2013)
Current ways of teaching requirements analysis, such as paper-based case studies, do not sufficiently support development of skills to investigate a problem situation. This paper reports on research to develop and evaluate an initial prototype of a Realistic Immersive Virtual Agent-based Learning Environment (RIVALE) virtual case study. The example fictional case study in this paper would be used as an exercise for students taking a systems analysis and design class to practice and learn requirements elicitation skills, such as interviewing, questionnaires, document review, form review, and observation. The intention is to provide a more realistic experience and to thereby support better learning as well as more realistic assessment of and feedback concerning student skills in requirements elicitation. The requirements, design, implementation, and initial, lightweight evaluation of the initial prototype are described. The initial prototype shows promise, but specific issues, especially problems with achieving realistic conversation, are identified and recommendations for further research are provided.,